1998
DOI: 10.2337/diacare.21.12.2144
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Kidney Function in Japanese Patients With Maturity-Onset Diabetes of the Young

Abstract: The results indicate that as in white patients, MODY resulting from mutations in the HNF-1 alpha, HNF-1 beta, and HNF-4 alpha genes in Japanese patients may be a severe disease similar to classic type 2 diabetes. In addition, they suggest that patients with HNF-1 beta diabetes may be characterized by diminished kidney function and perhaps abnormal liver function. Further studies are needed to determine whether tests of liver and kidney function will be useful in the diagnosis and subclassification of MODY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 20 publications
1
56
1
3
Order By: Relevance
“…These results were in agreement with those reported in other populations. 22,23 On the other hand, over half of the MODYX subjects were overweight, compared to only 24% in the MODY3 subjects. Furthermore, the higher BMI and triglyceride, lower HDL and a higher prevalence of hypertension in MODYX subjects suggested the presence of greater insulin resistance compared to the MODY3 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with those reported in other populations. 22,23 On the other hand, over half of the MODYX subjects were overweight, compared to only 24% in the MODY3 subjects. Furthermore, the higher BMI and triglyceride, lower HDL and a higher prevalence of hypertension in MODYX subjects suggested the presence of greater insulin resistance compared to the MODY3 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…HNF-4(R127W) mutation in these individuals is not a functional mutation but rather is a rare polymorphism and therefore does not lead to altered HNF-4␣-dependent gene expression (23,25). The other study, which reports a family with a HNF-4(R154X) mutation, found elevated Lp(a) levels and no significant differences in apo(AII), apo(CIII), and triglyceride levels (24).…”
Section: Genotype/phenotype In Hnf-4␣/mody1mentioning
confidence: 97%
“…TCF2 adult patients have mild to moderate renal failure in the absence of diabetic nephropathy (18). Moreover, pancreatic atrophy, urogenital abnormalities, abnormal liver enzyme levels, and hyperuricemia are observed in patients with TCF2 mutations (12)(13)(14)19,20). Prenatal forms also were described but only as a case report: Cystic renal dysplasia (8,9,12,16), bilateral hyperechogenic kidneys (14,21), renal agenesis, pelvicaliceal dilation, and multicystic dysplastic kidney (14).…”
mentioning
confidence: 99%